Analysis of Immunization, Adverse Events, and Efficacy of a Fourth Dose of BNT162b2 Vaccine in Health Workers in Mexico, a Pilot Study - Maria Elena Romero-Ibarguengoitia; Arnulfo González-Cantú; Diego Rivera-Salinas; Yodira Guadalupe Hernández-Ruíz; Ana Gabriela Armendariz-Vázquez; Irene Antonieta Barco-Flores; Rosalinda González-Facio; Miguel Ángel Sanz-Sánchez (Vaccines, 2022)
There is scarce information on seroconversion and adverse events after immunization (AEFI) with the fourth dose of BNT162b2. Our aim was to correlate the magnitude of the antibody response to this vaccination regimen in terms of clinical conditions and AEFI. This was an observational pilot study in which SARS-CoV-2 S1–S2 IgG antibodies titers were measured 21–28 days after the first and second dose, three months after the second dose, 1–7 and 21–28 days after the third dose, before the fourth dose, and 21–28 days after the fourth dose. We recruited 112 subjects in a hospital in Mexico, 74% women, with an average age of 43 (SD 9) years. After the first dose, subjects had a median IgG AU/mL (IQR) of 122 (1904) that increased to 1875 (2095), 3020 (2330), and 4230 (3393) 21–28 days after the second, third, and fourth doses, respectively (p < 0.01). The number (%) who experienced any AEFI between the first and fourth doses was 90 (80.4), 89 (79), 65 (58), and 69 (61.5), respectively (p < 0.001). After the fourth dose, the most frequent of AEFI was pain at the injection site (87%). There was a correlation between AEFI and gender after the fourth dose, as well as with antibody levels (p < 0.05). During the Omicron outbreak, six (5.3%) had mild COVID-19 for 8–28 days after the fourth dose. The median increase in S1/S2 IgG was 30.8-fold after the fourth BNT162b2 dose when compared with the first dose and caused mild AEFI.